2001
DOI: 10.1046/j.1365-2141.2001.02809.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic type 1 protein C deficiency caused by a de novo Ser270Leu mutation in the catalytic domain

Abstract: Summary. Heterozygosity for a C8524T transition in the protein C gene converting Ser270(TCG) to Leu(TTG) in the protease domain was identified in a family with venous thrombosis. The mutation was associated with parallel reduction in plasma levels of protein C anticoagulant activity and protein C antigen, which is consistent with a type 1 deficiency. Transient expression of mutant protein C cDNA in human kidney 293 cells and analysis of protein C antigen in culture media and cell lysates showed that the secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In vitro studies of various mutations in the PROC gene have provided insight into how these mutations can cause PC deficiency [7-15,20,28]. Most of these studies revealed that the PC deficiency was due to impaired secretion caused by intracellular degradation of the mutated proteins [8,10,11,15,20,28]. Enhanced proteolytic degradation of mutated proteins is a common molecular pathological mechanism in many diseases [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of various mutations in the PROC gene have provided insight into how these mutations can cause PC deficiency [7-15,20,28]. Most of these studies revealed that the PC deficiency was due to impaired secretion caused by intracellular degradation of the mutated proteins [8,10,11,15,20,28]. Enhanced proteolytic degradation of mutated proteins is a common molecular pathological mechanism in many diseases [30].…”
Section: Discussionmentioning
confidence: 99%
“…Results from these studies indicated that mutated PC variants were secreted inefficiently from transfected cells compared to wild-type (WT) PC [7-15]. Some of the studies also demonstrated that the intracellular levels of the mutated PC were decreased compared to WT PC, suggesting increased intracellular degradation of the mutated PC to be a dominant pathway behind the impaired secretion [8,10,11,15]. …”
Section: Introductionmentioning
confidence: 99%
“…16 Cell culture, transfection and phenotype assays COS-7 cells were cultured in Dulbecco modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 2 mM L-glutamine, 100 U/ mL penicillin G and 100 mg/mL streptomycin in a 5% CO 2 atmosphere at 378C. 16 Cell culture, transfection and phenotype assays COS-7 cells were cultured in Dulbecco modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 2 mM L-glutamine, 100 U/ mL penicillin G and 100 mg/mL streptomycin in a 5% CO 2 atmosphere at 378C.…”
Section: Construction Of Expression Vectors and Site-directed Mutagenmentioning
confidence: 99%
“…The Protein C activity and antigen concentration in plasma were analysed by Stachrom™ Protein C and Asserachrom™ Protein C, respectively (both Diagnostica Stago, Asnieres-Sur-Seine, France). Protein C antigen in cell lysate and media were analysed by ELISA using polyclonal antibodies as described (18,19). Determination of antithrombin, activated protein C resistance and total protein S in plasma was performed using COAMATIC ® Antithrombin (Chromogenix, Mölndal, Sweden), COATEST ® APC™ Resistance V (Chromogenix) and Assera™-plate protein S (Diagnostica Stago), respectively.…”
Section: Assay Of Protein C and Other Biochemical Assaysmentioning
confidence: 99%
“…Isolation of genomic DNA from peripheral blood cells, analysis of the protein C gene and assay of the Arg506Gln Leiden mutation in the coagulation factor V gene and the G20210A transition in the prothrombin gene was performed as described (19).…”
Section: Assay Of Protein C and Other Biochemical Assaysmentioning
confidence: 99%